Retrospective Evaluation of the Outcomes of Splenectomy in Patients with β-Thalassemia: Insights from a Tertiary Care Center in Bahawalpur - Muhammad Irfan khan; Faseeh Abid; Hafsa Malik; Nadeem Shahid Younas; Ayesha Sarfaraz; Nausherwan Malik; Haris Irfan Khan (Life and Science)
Objective: To evaluate outcomes of splenectomy in patients with β-thalassemia major. Study Design: A retrospective study. Place and Duration of Study: The study was conducted at the Department of Hematology, Bahawal Victoria Hospital Bahawalpur, Pakistan, from June 2022 to June 2023. Methods: A total of 80 patients with β-thalassemia were included. Participants were divided into Group A (n=40), including patients who had undergone splenectomy, and Group B (n=40), including patients with no splenectomy. The medical records of all participants were reviewed.  Complete blood count, serum ferritin, and liver function tests were recorded. Flow cytometry was used to assess lymphocyte populations. Patients in Group A were evaluated 2 years after the splenectomy. Results: Mean platelet and white blood cell count after splenectomy were 645.700/mm3 and 16.480/mm3 respectively. Splenectomy resulted in a significant increase in RBC indices, hematocrit, RBC count, and mean hemoglobin level. However, splenectomy did not decrease iron burden, and more patients required iron chelation. Group B had significantly higher total and indirect bilirubin compared to Group A. Splenectomy resulted in a significant increase in total and B lymphocytes. However, Group A had lower IgM Memory B lymphocytes than Group B. CD4 helper T lymphocytes, in total T lymphocytes, CD4+/CD8+ ratio and CD8 cytotoxic T lymphocytes did not differ significantly between both groups. Conclusion: Splenectomy is associated with the risk of thrombocytosis in the long term. It improves anemia but does not impact blood transfusion requirement or iron burden. Preoperative vaccination can reduce the risk of overwhelming post splenectomy infections.